Sistem Informasi Geografis Pemetaan Permainan Tradisional di Indonesia dengan Rapid Application Development Berbasis Website - Amini, Raissa; Abdullah, Atje Setiawan; Pradana, Aditya (Jurnal Telematika, 2022)
Indonesia is one of the largest archipelagic countries in the world with a very diverse culture. One of them is a traditional game. Along with the times, traditional games began to be abandoned by society. Many traditional games in each region are still unknown to the public because the information is not managed and systematic. Therefore, it is necessary to develop a web-based geographic information system for mapping traditional games in Indonesia. Web development in this study uses the Rapid Application Development (RAD) method which aims to shorten the time with 4 phases (Requirements Planning, User Design, Construction and Cutover). The end result of this research is a website-based system with user and admin features. The main user feature is an interactive map of the spread of traditional games, while the admin feature is data management for traditional games, provinces and admin. The results of system testing with black-box testing are as expected. Testing with UEQ obtains a scale value above 2 which means positive and an excellent benchmark. From these results, it's known that the development of a web-based geographic information system mapping traditional games in Indonesia is feasible to use.